1996
DOI: 10.1097/00000658-199606000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up After Bilioenteric Anastomosis for Benign Bile Duct Stricture

Abstract: ObjectiveThe authors provide a prospective evaluation of long-term results after bilioenteric anastomoses for benign biliary stricture. Summary Background DataWith the advent of laparoscopic techniques, the frequency of bile duct injury after operation has increased. Reports on the operative management of these injuries have not provided long-term follow-up. Over a similar period, reports of both endoscopic and invasive radiographic methods as primary treatment for bile duct stricture have compared success rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 14 publications
(5 reference statements)
1
58
0
2
Order By: Relevance
“…It has been reported that patients with bile duct stricture or injury when operative repair was performed they have had excellent results at tertiary expert referral centers (32)(33)(34)(35)(36). In several series of operative repair the mortality observed was very low (0% to 3%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that patients with bile duct stricture or injury when operative repair was performed they have had excellent results at tertiary expert referral centers (32)(33)(34)(35)(36). In several series of operative repair the mortality observed was very low (0% to 3%).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have presented data that a minority of bile duct injuries (8% to 33%) referred to tertiary care centers have been recognized at the time of LC (32)(33)(34)(35)(36). Usually, unexplained bile drainage raises the suspicion of a biliary injury.…”
Section: Recognized At Lcmentioning
confidence: 99%
“…Although surgery has the theoretical advantage of being definitive, 4 endoscopic stent placement has gained acceptance as an initial treatment because of its simplicity and low morbidity and mortality.…”
Section: 류충헌 등 양성 담도협착에서 완전 피막형 금속 스텐트 삽입의 효과mentioning
confidence: 99%
“…Optimal management of an IBDI depends on several factors, including type of injury, associated vascular injuries, condition of the patient, timing of reconstruction and availability of expertise, and includes open surgical and endo-therapeutic options [2]. Reconstructive hepaticojejunostomy which is commonly performed, is associated with low mortality and low morbidity [3,4]. Minor injuries can be managed endoscopically with comparable success rates [5][6][7].…”
Section: Introductionmentioning
confidence: 99%